World-Class leadership thinking - Eyam-Ozung, Philip (Lagos, Nigeria : enterprise Strategies Consulting Limited, 2011)
Provides a model of leadership thinking that can help leaders and leadership aspirants develop the distinctive leadership capabilities and disciplines that will facilitate their emergence as world-class leaders.
Includes index
oif 23/12/13
Loan
Keywords: .Leadership